Supplementary toy development for children with the multiple disabilities in Nakhon Si Thammarat - Weerapong, Pongtep; Numnaphol, Ubonrat (Asia-Pacific Journal of Science and Technology, 2017)
This research presents a User centered design approach for development both balance and mobility skills forchildren with disabilities. The purpose of this research was to compare the effectiveness for new toys of children withdisabilities as follow as: 1) sitting balance; 2) body balance; 3) gross motor (limb); and 4) hand manipulation skills. Of the total sample, 5 to 13 years children with disabilities (N = 10) in Nakhon Si Thammarat province. As new toys, the well-designed has produced to protect the safety and effective clinical care for patients. The validation and reliability was tested by the division of health and safety at Maharaj Nakhon Si Thammarat Hospital and Special Education Center at Nakhon Si Thammarat and Nakhon Si Thammarat Rajabhat University. Data was collected by users’ recommendation with onsite-observation and satisfaction evaluation form. Data was analyzed by SWOT Analysis and the TOWS matrix. The results revealed that the appropriate integrated methods with two design and ergonomics represented by the toy design process. A case study conducted the procedural design of toys for ten children with disabilities. Moreover, each toy have been adjusted its application for physical disabled and anthropometry individuals was established and tested. The finding has gained from users’ and evaluation various cases in the early part of the research. The prototype toy served as a design process; for example, the entire design process, using the process, an adjustable dimension for physically disabled individuals. The existing benefit found that new toys can be applied, and these toys did improve the sitting balance, body balance, gross motor (limb) and hand manipulation skills with multiple disabilities. However, they were also interference with one’s ability to maintain balance in certain situations, and the strength towards the quality of life as sustainability development.